"A New Type of Believer": Transformations of Religiosity in the Regions of Post-Soviet Russia (On the Example of Khakassia) - Aksutin, Yuri Mikhailovich; Kochina, Elena Alexandrovna (KnE Social Sciences, 2021)
The purpose of this article is to represent the research results and modeling of the features of the transformation of the Southern Siberia inhabitants’ religiosity (Khakassia), as well as the specifics of their demographic characteristics. It presents an overview of the main approaches to the analysis of religiosity in the context of modern transformations. In particular, the author focuses on the conflict between the traditional stereotype, according to which older people, women and people with a low level of education predominate among believers, and religious identification is carried out exclusively by traditional mechanisms, and hypotheses about the formation of a new type of believer (new religiosity) in post-Soviet Russia. It is emphasized that the analysis and characterization of the phenomenological features of religiosity has its own difficulties (problems of determining the criteria of religiosity).This religiosity has a significant conflict potential. The article is based on the results of a mass surveys carried out by the method of formalized interviewing, by the authors in the South Siberian Republic of Khakassia. The author comes to a reasoned conclusion that the religious situation has undergone serious changes. On the one hand, the appeal to traditional identities was inevitable in the conditions of the disappearance of integration Soviet consciousness and the growth of religiosity solved the problem of gaining a sense of community, reinforced ethnic and national identities in the first post-Soviet years. The growth of religiosity was abrupt. However, the existence of a close relationship between religious (confessional) and ethnic identity was not identified in recent years. In addition, the results of the 2018–2019 surveys suggest that a certain ‘limit of growth’ of the society’s religiosity has been reached. On the other hand, a new type of believer in Russia, judging by the current model, has already survived childhood illnesses. The results of the study show that there are more believers among older people. However, age and gender differences, as well as the level of education, are no longer fundamental. In Russia, a new type of believer has appeared — a young person with a fairly high level of education, who often makes a conscious choice of a denomination and performing religious rituals, having a functional self-identification with a particular religious tradition. Keywords: religiosity, confessional identity, modernization, traditionalism